2023
DOI: 10.1002/slct.202301834
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic [3+2] Cycloaddition Reaction: Synthesis of Fully Decorated Sulfonyl 1,2,3‐Triazoles as Potent EGFR Targeting Anticancer Agents**

Venkat Reddy Dodlapati,
Tatipelly Madhukar Reddy,
Mohammad Azam
et al.

Abstract: A general strategy was developed for the synthesis of new fully decorated sulfonyl1,2,3‐triazolyl imidazoles from β‐ketosulfones and several aryl sulfonyl azides using the ramachary organocatalytic cycloaddition method. Organocatalytic [3+2] cycloaddition reaction of β‐ketosulfone acts as an internal alkyne, as reported for the synthesis of sulfonyl‐1,2,3‐triazolyl imidazoles at 80 °C in good to excellent yields of products in the presence of catalytic amounts of pyrrolidine (10 mol %). In vitro anticancer act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…[60][61][62][63] Among them, hybrids 37a breast cancer cell lines demonstrated that electron-withdrawing group at R2 position was beneficial for the activity. [64] Among them, was superior to doxorubicin (IC 50 : 650 nM). [65] The SAR revealed that the amide linker between 1,2,3-triazole and phenyl ring was critical for the activity, and replacement of thioether linker between 1,2,3triazole and imidazole by phenyl ring or indole decreased the activity significantly.…”
Section: 23-triazole-azole Hybridsmentioning
confidence: 96%
“…[60][61][62][63] Among them, hybrids 37a breast cancer cell lines demonstrated that electron-withdrawing group at R2 position was beneficial for the activity. [64] Among them, was superior to doxorubicin (IC 50 : 650 nM). [65] The SAR revealed that the amide linker between 1,2,3-triazole and phenyl ring was critical for the activity, and replacement of thioether linker between 1,2,3triazole and imidazole by phenyl ring or indole decreased the activity significantly.…”
Section: 23-triazole-azole Hybridsmentioning
confidence: 96%
“…All of the synthesized (5a-5o) compounds were tested for anti-breast cancer activity against two breast cancer cell lines, MDA-MB-231 and MCF-7, using the MTT assay [37], and the results were compared with the standard drug erlotinib (Table 2). Some of the compounds were found to have good action against both MCF- The nature of the phenyl ring attached to 1st position of a 1,2,3-triazole moiety that affects anti-breast cancer activity was described using a SAR study.…”
Section: Anti-breast Cancer Activitymentioning
confidence: 99%